2017
DOI: 10.18632/oncotarget.23727
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach identifies new oncotargets in melanoma

Abstract: Melanoma is an aggressive skin cancer; an early detection of the primary tumor may improve its prognosis. Despite many genes have been shown to be involved in melanoma, the full framework of melanoma transformation has not been completely explored. The characterization of pathways involved in tumor restraint in in vitro models may help to identify oncotarget genes. We therefore aimed to probe novel oncotargets through an integrated approach involving proteomic, gene expression and bioinformatic analysisWe inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The Warburg effect has been hypothesised to be an adaptation mechanism in cancer cells to support the biosynthetic requirements of rapid proliferation. Alpha-enolase expression has been shown to be altered at the mRNA and/or protein level in a range of tumours [ Table 1], and generally upregulated in most, including acute myeloid leukaemia (AML), glioma, melanoma, lymphoma, and colorectal, endometrial, gastric, head and neck, liver, ovarian and pancreatic cancer [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Alpha-enolase Expression Is Altered In Tumours and Varies Wimentioning
confidence: 99%
See 1 more Smart Citation
“…The Warburg effect has been hypothesised to be an adaptation mechanism in cancer cells to support the biosynthetic requirements of rapid proliferation. Alpha-enolase expression has been shown to be altered at the mRNA and/or protein level in a range of tumours [ Table 1], and generally upregulated in most, including acute myeloid leukaemia (AML), glioma, melanoma, lymphoma, and colorectal, endometrial, gastric, head and neck, liver, ovarian and pancreatic cancer [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Alpha-enolase Expression Is Altered In Tumours and Varies Wimentioning
confidence: 99%
“…Increased glycolysis is considered a hallmark of cancer [2] and investigating glycolytic enzymes may yield new therapeutic approaches for cancer treatment. Enolases are key glycolytic enzymes [3] , and increased expression of one isoform, a-enolase, has been identified in several cancer types [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . This review provides an overview of the expression of a-enolase and key functions it controls in cancer cells, with a focus on the potential role of a-enolase as a cancer prognostic biomarker or therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma cells invade skin tissue and enter blood vessels, forming metastases at distant sites [ 2 ]. In addition, we have found that STMN1, a cytosolic phosphoprotein [ 3 ], and SSBP1, involved in p53 transcriptional activity [ 4 ], are up- and down-regulated, respectively, in melanoma cells and that their modulation is involved in melanoma transformation [ 5 ]. It has also been reported that the mutation rate in melanoma is higher than in other solid malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mutations in cyclin-dependent kinase inhibitor 2A (CDKN2A) encoding two tumour suppressor proteins, p16 and p14, as well as genes involved in the DNA repair mechanism or the melanocortin-1 receptor (MC1R) play an important role in the onset of melanoma 2,6 . We recently reported new melanoma oncotargets, such as enolase 1, parkinsonism-associated deglycase, prostaglandin E synthase 3, nucleophosmin, and stathmin 1, playing a key role in malignant transformation 7 . Moreover, molecular analyses showed the central role of the PTEN/mutated in multiple advanced cancers 1 (MMAC1) in reducing cell proliferation or inducing apoptosis 8 , and the association of PTEN loss to melanoma 9 .…”
Section: Introductionmentioning
confidence: 99%